Fifteen Years On, Where Are We in the War on Terror? - Jenkins, Brian Michael
Measuring progress in irregular warfare without frontlines is always difcult. The various dimensions and multiple fronts of the United States ongoing campaign against terrorists make it an exceptional challenge. And much has changed since that campaign began 15 years ago. There has not been another 9/11-scale event. Although they attract followers, neither al-Qa`ida nor its progeny has become a mass movement. The constellation of groups claiming allegiance to them is far from an efective alliance, and the Islamic State has been contained. The leaders of al-Qa`ida depend heavily on exhortation to get others to fight, and the turnout is thin. On the other side of the ledger, the targeted groups have survived, their determination seems undiminished, and their ideology remains powerful. They are deeply embedded in a number of fragile, divided, conflict-ridden states. Persistent foes, they are able to operate underground and capable of comebacks if pressure on them subsides. The conflict will go on.
Keywords: Atentados del 11 de Septiembre, Estados Unidos, 2001